Environmental concern and intention to adopt green concepts among housing developers in Klang Valley, Malaysia - Lau, Nur Jasmine Leby (2015)
Environmental degradation caused by construction activities has raised concern regarding sustainability issue. Although developers are showing interest in sustainable construction, the implementation is not industry wide. General environment beliefs are believed to have effect on developers’ behaviour. Therefore understanding their environmental worldviews enables the assessment of their attitudes about green concepts, which helps in anticipating behaviour intention to adopt the concept in future housing projects and devising necessary intervention to behavioural change. The objectives for this study are (1) to explore the structure of the environmental concern scale that is the New Ecological Paradigm (NEP) scale, (2) to determine the predictability of attitude, subjective norm and perceived behavioural control (PBC) toward the intention to adopt green concept, (3) to determine the mediating role of attitude, subjective norm and PBC on the relationship between environmental concern and intention to adopt green concepts and (4) to determine the mediating role of attitude, subjective norm and PBC on the relationship between the sub-dimensions of environmental concern and intention to adopt green concepts. A cross-sectional survey was conducted among developer organisations in Klang Valley and 87 usable questionnaires were returned, yielding a response rate of 24.5%. In addition, in-depth interviews were conducted with five project managers to gain more insights on specific issues of concern and the findings were used to support statistical outcomes. An examination of total pro-NEP score indicated a moderate level of environmental concern among respondents. High scores on both pro-NEP and pro-DSP items revealed that there was a co-existence of both ecological and anthropocentric view of the environment and this was further supported by the in-depth interviews. Factor analysis supported the multidimensionality claim of the environmental concern scale where four distinctive dimensions were found, namely Human over nature, Eco-crisis, Rights of nature and Limits of growth. These factors explained 61.6% of the variance and each has acceptable internal consistency. Multiple regression analysis revealed that the prediction model was statistically significant and accounted for approximately 67% of the variance in intention to adopt green concepts. PBC was the best predictor, followed by subjective norm and attitudes. This was supported by the interview outcomes where informants shared a stronger sentiment on factors that facilitate or impede the adoption of green concepts in housing projects. Multiple mediation analysis with bootstrapping technique was used to test the effect of environmental concern and its facets on intention to adopt green concepts through attitude, subjective norm and PBC. Results revealed that eco-crisis facet has significant direct relationship with attitude as well as behavioural intention. PBC was found to be a significant mediator for the relationship between environmental concern and human over nature with behavioural intention. In the mediation model between eco-crisis dimension and behavioural intention, apart from PBC, attitude was found to be another significant mediator of the relationship. It is concluded that in general respondents held a moderate pro-NEP perspective with the coexistence of both an ecological and a human dominance view of the environment. The contribution of PBC in predicting intention implied that organisations tend to exhibit stronger intention to adopt green concepts when they perceive they have adequate resources, opportunities and skills. In addition, PBC was a vital mediator in explaining the relationship between environmental concern and its sub-dimensions of human over nature and eco-crisis with intention to adopt green concepts. The NEP scale was proven to be a reliable and valid measurement tools in developing countries like Malaysia. The integration of general environmental concern and the Theory of Planned Behaviour (TPB) was meaningful and has contributed new insights on behavioural intention. In addition, the use of the sub-dimensions of environmental concern has extended understanding on environmentalism. Bootstrapping techniques has proven its utility in unveiling potential mediators in small sample size even when total effect is insignificant. Practically, government needs to strengthen the concern for eco-crisis through various educational programmes and trainings. In addition, the public sector needs to walk the talk by moving toward a more sustainable development path. Regulations and financial benefits can be used to expedite the uptake of green concepts among housing developers. Consumers should also be made aware of their roles as ecological citizenship that could help in protecting and restoring the natural environment.